INTERTIDAL BEACH SLOPE PREDICTIONS COMPARED TO FIELD DATA - Madsen A.J.; Plant N.G. (My University, 2001)
This paper presents a test of a very simple model for predicting beach slope changes. The model assumes that these changes are a function of both the incident wave conditions and the beach slope itself. Following other studies, we hypothesized that the beach slope evolves towards an equilibrium value that depends nonlinearly on wave steepness (H/L). The rate of beach slope response is assumed to depend on both the degree of slope disequilibrium and on the incident wave energy. The model was tested against daily beach slope observations derived from digital images of the nearshore zone. Approximately, 104 images were analyzed over eight, mostly consecutive, month-long periods along a 2km length of beach. The slope change model was calibrated by fitting it to the daily differences in the alongshore-averaged slopes, which were obtained from a 500m (alongshore) subset of the observations. An equilibrium slope prediction proportional to the wave steepness (H/L) raised to the -1st to -2nd power performed best compared to several alternative models. The response rate of beach slope changes depended on the wave height, raised to the 3rd or 4th power. A characteristic response time for the system was found to be 1-2days. The calibrated (i.e. hindcast) model explained 30-40% of the observed slope change variance, indicating that the model was consistent with the data. However, when the model was used to predict the evolution of the beach slope time series (i.e. to forecast), the prediction error variance was equal to or only slightly lower than the observed temporal variability in the slopes. The present model is sufficiently accurate to characterize beach slope dynamics, but its predictive capability would not outperform a model that predicts a constant, mean slope.
Keywords: VIDEO IMAGES; EQUILIBRIUM; HINDCAST; FORECAST